CRISPR/Cas9 Genome Editing Using Gold‐Nanoparticle‐Mediated Laserporation. Issue 11 (29th May 2018) - Bošnjak, Berislav; Permanyer, Marc; Sethi, Maya K.; Galla, Melanie; Maetzig, Tobias; Heinemann, Dag; Willenzon, Stefani; Förster, Reinhold; Heisterkamp, Alexander; Kalies, Stefan
Abstract: Engineered nucleases hold large potential for future gene therapy applications. An obstacle hampering their applications are delivery methods bearing efficiency, throughput, and viability of target cells. How this limitation can be overcome via gold‐nanoparticle‐mediated (GNOME) laserporation is demonstrated. It employs a picosecond laser setup and 200 nm gold nanoparticles, and its full capacity with CRISPR/Cas9 delivery is demonstrated. 70 kDa dextrans are utilized to probe delivery in adherent SC1 cells. Afterward, GNOME laserporation is used for transfection of crRNA:tracrRNA targeting the mouse CCR7 (mCCR7) into SpCas9 (Streptococcus pyogenes Cas9) and mCCR7 co‐expressing SC1 cells. Finally, ribonucleoprotein particles consisting of mCCR7 crRNA:tracrRNA and SpCas9 endonuclease are transfected into SC1 cells not expressing SpCas9. Gene knockout efficiencies of up to 65% are detected in the GNOME laserporated cells. To validate the simplicity of the approach, the same treatment parameters are used to successfully knock out CXCR3 in 25% of GNOME laserporated activated mouse CD8 + T cells. In conclusion, this is the first demonstration of the unique combination of nanotechnology and laser irradiation for gene editing via engineered nucleases. Abstract : Gold‐nanoparticle‐mediated laser transfection (GNOME laserporation) uses short pulsed laser irradiation of gold nanoparticles sedimented on the plasma membrane. The irradiation creates nanobubbles that permeabilize the membrane allowing entry of small molecules into the cell. In this study, GNOME laserporation successfully delivers guide‐RNA and/or guide‐RNA/Cas9 ribonucleoprotein particles into cell lines and primary cells for CRISPR/Cas9 genome editing.